(untitled) (Biological Sciences - PJSIR, 1994)
The total lipids of Carum capticum were fractionated by thin-layer chromatography into hydrocarbons (1.2%), wax esters (2.0%), sterol esters (1.8%), triglycerides (54.l %), fatty acids (5.7%),1:3 diglyceridcs (5.7%),1:2 diglycerides (6.7%), glycolipids (7.2%), 2-monoglycerides (3.9%), I-monoglycerides (7.4%), phosphatidyl ethanolamines (1.5%) phosphatidyl cholines (1.1 %) Iysophosphatidyl ethanolamines (0.6%) and phosphatidyl inositols (1.1%).